A kind of aging-resistant polyurethane-zirconium phosphate composite modified asphalt and preparation method thereof
By using organic zirconium phosphate and isocyanate prepolymers to form a crosslinking network in polyurethane modified asphalt, the problem of poor anti-aging performance of traditional polyurethane modified asphalt is solved, and higher anti-aging and high-low temperature performance is achieved, and the asphalt is extended The service life of the road surface.
Patent Information
- Application Number
- CN202411379632.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Traditional polyurethane modified asphalt has poor anti-aging properties and is difficult to meet the requirements of road materials to withstand high-energy ultraviolet rays and high-temperature performance during long-term service.
Organic zirconium phosphate and polyurethane composite modified asphalt is prepared by ultrasonic intercalation treatment, and its layered structure absorbs ultraviolet rays and forms a crosslinking network with isocyanate prepolymers to improve the anti-aging ability and high and low temperatures of asphalt performance.
It significantly improves the anti-aging performance and high and low temperature performance of asphalt, extends the life of asphalt pavement, and can meet the high requirements for road material performance in the growing traffic load and harsh environment.
Smart Images

Figure BDA0005069573500000111 
Figure BDA0005069573500000112 
Figure BDA0005069573500000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building material preparation, and in particular relates to an aging-resistant polyurethane-zirconium phosphate composite modified asphalt and a preparation method thereof. Background Art
[0002] Asphalt pavement is widely used because of its good flatness, short construction period, and easy maintenance. However, ordinary asphalt pavement has poor road performance and is prone to road diseases, which seriously affects driving comfort and safety. With the continuous development of the road construction field, the demand for asphalt materials has also increased. Modifying asphalt is one of the main means to improve asphalt performance. As a new type of road material, polyurethane modified asphalt has gradually attracted the attention of scientific researchers, and its road performance has been widely recognized. Chinese patent CN102850506A discloses that asphalt and allyl alcohol are reacted to prepare hydroxyl-containing asphalt, and then reacted with isocyanate to obtain polyurethane modified asphalt, which greatly improves the low-temperature brittleness and poor flexibility of ordinary asphalt. Chinese patent CN106317371B discloses a castor oil-based polyurethane modified asphalt, and the prepared modified asphalt has a higher softening point and better high-temperature performance. However, asphalt contains a large number of organic molecules, and the polyurethane structure has groups that are prone to oxidation reactions, so the anti-aging performance of traditional polyurethane modified asphalt is poor, which seriously affects the long-term service performance of polyurethane modified asphalt pavement.
[0003] During the service of asphalt pavement, high-energy ultraviolet radiation is the main cause of asphalt material aging. Adding modifiers to modify asphalt is one of the effective ways to improve the asphalt's resistance to ultraviolet aging. In this regard, polyurethane modified asphalt, in existing studies, usually adds modified inorganic substances and bio-based materials with antioxidant functions to improve the anti-aging ability of polyurethane asphalt. For example, Chinese patent CN108485292A proposes a method for preparing a polyurethane / organized montmorillonite composite modified asphalt, which uses polyurethane prepolymers and OMMT (montmorillonite) to chemically modify ordinary road petroleum asphalt to improve the anti-aging performance of polyurethane asphalt. Chinese patent CN113861701B successfully improved the anti-aging performance of polyurethane modified asphalt by adding pretreated biomass heavy oil.
[0004] In order to broaden the types of modified asphalt, the present invention proposes for the first time asphalt modified with zirconium phosphate and polyurethane, which fills the gap in the preparation process of zirconium phosphate in modified asphalt. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes an aging-resistant polyurethane-zirconium phosphate composite modified asphalt and a preparation method thereof. The method adopts organic zirconium phosphate and polyurethane composite modified asphalt, wherein the organic zirconium phosphate has the function of absorbing ultraviolet rays and can also act as a cross-linking agent to form a polyurethane cross-linking network with isocyanate prepolymer, thereby improving the asphalt's anti-aging ability and high and low temperature performance.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] An aging-resistant polyurethane-zirconium phosphate composite modified asphalt comprises the following components in parts by weight: 100 parts of base asphalt, 3-15 parts of isocyanate prepolymer, 1-8 parts of organic zirconium phosphate, 0.001-0.1 parts of catalyst and 2-5 parts of solubilizer.
[0009] Furthermore, the organic zirconium phosphate is prepared by ultrasonically intercalating zirconium phosphate with organic molecules.
[0010] The layered structure of zirconium phosphate can effectively absorb ultraviolet rays. Inserting organic molecules into the interlayer of zirconium phosphate can increase the compatibility of zirconium phosphate particles with asphalt.
[0011] Furthermore, the organic molecules include polyols and / or polyamines. In addition to the active groups consumed by the intercalation of zirconium phosphate, the remaining active groups in the organic molecules with multiple active groups react with the isocyanate prepolymer to form a cross-linked structure, thereby improving the performance of asphalt.
[0012] Furthermore, the organic molecule is preferably a long-chain diamine or a long-chain polyamine. In the zirconium phosphate intercalation process, -NH2 has a higher priority than -OH, so amine molecules are easier to intercalate than alcohols. In addition, the zirconium phosphate particles have a stronger affinity with asphalt after combining with the long-chain structure, which can effectively improve the storage stability of the modified asphalt.
[0013] Furthermore, the molar ratio of the organic molecule to the zirconium phosphate is (0.5-2):1.
[0014] More specifically, compared with traditional mechanical stirring and electromagnetic stirring, ultrasonic intercalation can achieve more complete solution mixing, better intercalation effect, and shorter intercalation time. The method for preparing the organic zirconium phosphate comprises the following steps:
[0015] S1. Mix zirconium phosphate and organic molecular material in a molar ratio of 1:(0.5-2);
[0016] S2, then add distilled water, control the liquid-solid ratio to 100mL / g, and perform ultrasonic treatment for 30 to 90min;
[0017] S3. The obtained product is centrifuged, washed, filtered, and vacuum dried to constant weight.
[0018] Furthermore, the base asphalt is road petroleum asphalt, preferably 70# base asphalt. 70# asphalt has relatively stable chemical properties, moderate viscosity, large market supply and relatively low price.
[0019] Furthermore, the isocyanate prepolymer includes a polyether isocyanate prepolymer and / or a polyester isocyanate prepolymer.
[0020] Furthermore, the isocyanate prepolymer is a polyether isocyanate prepolymer with a molecular weight of 1000 to 5000 and an -NCO content of 3% to 18%. The polyether isocyanate prepolymer has good softness and elasticity and relatively low cost. The isocyanate prepolymer with the above molecular weight and -NCO content range can provide suitable reactivity and physical properties.
[0021] Further, the solubilizing agent includes one or more of dioctyl maleate, furfural extracted oil, epoxidized soybean oil and cashew nut shell oil, preferably cashew nut shell oil. Cashew nut shell oil, as a green and renewable bio-based material, has a large number of active groups in its structure. While playing a solubilizing effect, it can also react with isocyanate prepolymer to generate a cross-linked network structure to promote the full reaction of isocyanate prepolymer. In addition, the cashew nut shell oil molecule contains a hindered phenol structure, which can capture free radicals and improve the anti-aging ability of asphalt.
[0022] The second technical solution of the present invention:
[0023] A method for preparing the aging-resistant polyurethane-zirconium phosphate composite modified asphalt comprises the following steps:
[0024] Weigh each component by weight, heat and keep the base asphalt warm, then add the organic zirconium phosphate, solubilizer, and catalyst and stir, then add the heat-treated isocyanate prepolymer, continue stirring and let stand to obtain the aging-resistant polyurethane-zirconium phosphate composite modified asphalt.
[0025] Furthermore, the base asphalt is heated to 125-150° C., and the isocyanate prepolymer is preheated to 80-100° C. to obtain a heat-treated isocyanate prepolymer.
[0026] Furthermore, the standing temperature is 80-120° C. and the standing time is 2-8 hours.
[0027] Compared with the prior art, the present invention has the following advantages and technical effects:
[0028] (1) Compared with the traditional organic layered inorganic modified asphalt, the aging-resistant polyurethane-zirconium phosphate composite modified asphalt of the present invention has a polyurethane cross-linked network structure, which can effectively improve the high and low temperature performance of asphalt and meet the high requirements of road material performance under the increasing traffic load and harsh environment.
[0029] (2) Compared with traditional polyurethane modified asphalt, the organic zirconium phosphate in the aging-resistant polyurethane-zirconium phosphate composite modified asphalt of the present invention has a layered structure, which can absorb ultraviolet rays and protect the organic molecules in the polyurethane asphalt from oxidation. Therefore, the aging-resistant polyurethane-zirconium phosphate composite modified asphalt of the present invention has excellent anti-aging performance, which is beneficial to prolonging the life of the asphalt pavement. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The embodiment of the present invention proposes an aging-resistant polyurethane-zirconium phosphate composite modified asphalt, comprising the following components in parts by weight: 100 parts of base asphalt, 3 to 15 parts of isocyanate prepolymer, 1 to 8 parts of organic zirconium phosphate, 0.001 to 0.1 parts of catalyst and 2 to 5 parts of solubilizer.
[0036] In a preferred embodiment of the present invention, the organic zirconium phosphate is prepared by ultrasonically intercalating zirconium phosphate with organic molecules. The more specific preparation method includes the following steps:
[0037] S1. Mix zirconium phosphate and organic molecular material in a molar ratio of 1:(0.5-2);
[0038] S2, then add distilled water, control the liquid-solid ratio to 100mL / g, and perform ultrasonic treatment for 30 to 90min;
[0039] S3. The obtained product is centrifuged, washed, filtered, and vacuum dried to constant weight.
[0040] In a preferred embodiment of the present invention, the organic molecule includes polyols and / or polyamines, preferably long-chain diamines or long-chain polyamines; the term "long chain" in the present invention refers to a carbon chain with a straight chain structure of 12 to 16 carbon atoms. The long-chain diamine is preferably 1,12-diaminododecane or butanediamine.
[0041] In a preferred embodiment of the present invention, the base asphalt is road petroleum asphalt, preferably 70# base asphalt.
[0042] In a preferred embodiment of the present invention, the isocyanate prepolymer includes a polyether isocyanate prepolymer and / or a polyester isocyanate prepolymer; more preferably, the isocyanate prepolymer is a polyether isocyanate prepolymer with a molecular weight of 1000 to 5000 and a -NCO content of 3% to 18%.
[0043] In a preferred embodiment of the present invention, the solubilizing agent includes one or more of dioctyl maleate, furfural extracted oil, epoxidized soybean oil and cashew nut shell liquid. The present invention has found through experimental comparison that these solubilizing agents have no significant difference in the effect on asphalt performance during the process of modifying asphalt, so the typical but non-limiting solubilizing agent in the preferred embodiment of the present invention is cashew nut shell liquid.
[0044] In a preferred embodiment of the present invention, the catalyst is dibutyltin dilaurate.
[0045] The embodiment of the present invention also provides a method for preparing the aging-resistant polyurethane-zirconium phosphate composite modified asphalt, comprising the following steps:
[0046] Weigh each component by weight, heat and keep the base asphalt warm, then add the organic zirconium phosphate, solubilizer, and catalyst and stir, then add the heat-treated isocyanate prepolymer, continue stirring and let stand to obtain the aging-resistant polyurethane-zirconium phosphate composite modified asphalt.
[0047] In a preferred embodiment of the present invention, the base asphalt is heated to 125-150° C., and the isocyanate prepolymer is preheated to 80-100° C. to obtain the heat-treated isocyanate prepolymer.
[0048] In a preferred embodiment of the present invention, the standing temperature is 80-120° C. and the time is 2-8 hours.
[0049] The raw materials used in the embodiments of the present invention are all commercially available, wherein the isocyanate prepolymer used is HC-6295 polyether isocyanate prepolymer purchased from Shanghai Hecheng Polymer Technology Co., Ltd., with a molecular weight of 2000-4000. Other specific information is shown in Table 1.
[0050] Table 1 Parameter information of polyether isocyanate prepolymer
[0051] HC-6295 unit Test data Testing standards Appearance (20℃) - Colorless transparent viscous liquid NCO% % 9.0±0.2 HG / T2409 Viscosity (80℃) mPa·s 800±200 GB / T12009.3
[0052] In the embodiments of the present invention, "parts" represent "parts by weight" unless otherwise specified.
[0053] The technical solution of the present invention is further illustrated by the following embodiments.
[0054] Example 1
[0055] (1) Preparation of organic zirconium phosphate
[0056] S1. Mix zirconium phosphate and 1,12-diaminododecane in a molar ratio of 1:1;
[0057] S2, then add distilled water, control the liquid-to-solid ratio to 100mL / g, and perform ultrasonic treatment for 60min;
[0058] S3. Centrifuge, wash, filter and vacuum dry the obtained product to constant weight to obtain organic zirconium phosphate.
[0059] (2) Preparation of polyurethane-zirconium phosphate composite modified asphalt
[0060] S1. Weigh the following components by weight: 100 parts of 70# matrix asphalt, 10 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 5 parts of organic zirconium phosphate prepared in step (1), 0.001 parts of catalyst (dibutyltin dilaurate) and 3 parts of solubilizer (cashew nut shell oil);
[0061] S2. Add 70# base asphalt into a stirring tank, heat and maintain the temperature at 140°C, then add organic zirconium phosphate, solubilizer and catalyst into the stirring tank and stir for 30 minutes;
[0062] S3, preheating the isocyanate prepolymer to 90°C, adding it to the stirring tank in step S2, and continuing stirring for 60 minutes;
[0063] S4. After stirring, place the mixture in a 100°C temperature environment and let it stand for 4 hours to obtain an aging-resistant polyurethane-zirconium phosphate composite modified asphalt.
[0064] Example 2
[0065] (1) Preparation of organic zirconium phosphate
[0066] S1. Mix zirconium phosphate and 1,12-diaminododecane in a molar ratio of 1:0.5;
[0067] S2, then add distilled water, control the liquid-solid ratio to 100mL / g, and perform ultrasonic treatment for 90min;
[0068] S3. Centrifuge, wash, filter and vacuum dry the obtained product to constant weight to obtain organic zirconium phosphate.
[0069] (2) Preparation of polyurethane-zirconium phosphate composite modified asphalt
[0070] S1. Weigh the following components by weight: 100 parts of 70# base asphalt, 3 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 1 part of the organic zirconium phosphate prepared in step (1), 0.1 part of catalyst (dibutyltin dilaurate) and 2 parts of solubilizer (dioctyl maleate);
[0071] S2. Add 70# base asphalt into a stirring tank, heat and maintain the temperature at 150°C, then add organic zirconium phosphate, solubilizer and catalyst into the stirring tank and stir for 30 minutes;
[0072] S3, preheating the isocyanate prepolymer to 80°C, adding it to the stirring tank in step S2, and continuing stirring for 60 minutes;
[0073] S4. After the stirring is completed, the mixture is placed in a temperature environment of 120° C. and allowed to stand for 8 hours to obtain an aging-resistant polyurethane-zirconium phosphate composite modified asphalt.
[0074] Example 3
[0075] (1) Preparation of organic zirconium phosphate
[0076] S1. Mix zirconium phosphate and 1,12-diaminododecane in a molar ratio of 1:2;
[0077] S2, then add distilled water, control the liquid-to-solid ratio to 100mL / g, and perform ultrasonic treatment for 30min;
[0078] S3. Centrifuge, wash, filter and vacuum dry the obtained product to constant weight to obtain organic zirconium phosphate.
[0079] (2) Preparation of polyurethane-zirconium phosphate composite modified asphalt
[0080] S1. Weigh the following components by weight: 100 parts of 70# base asphalt, 15 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 8 parts of organic zirconium phosphate prepared in step (1), 0.001 parts of catalyst (dibutyltin dilaurate) and 5 parts of solubilizer (epoxidized soybean oil);
[0081] S2. Add 70# base asphalt into a stirring tank, heat and maintain the temperature at 125°C, then add organic zirconium phosphate, solubilizer and catalyst into the stirring tank and stir for 30 minutes;
[0082] S3, preheating the isocyanate prepolymer to 100° C., adding it to the stirring tank in step S2, and continuing stirring for 60 minutes;
[0083] S4. After the stirring is completed, the mixture is placed in a temperature environment of 80° C. and allowed to stand for 2 hours to obtain an aging-resistant polyurethane-zirconium phosphate composite modified asphalt.
[0084] Example 4
[0085] (1) Preparation of organic zirconium phosphate
[0086] S1. Mix zirconium phosphate and diaminodiamine in a molar ratio of 1:1;
[0087] S2, then add distilled water, control the liquid-to-solid ratio to 100mL / g, and perform ultrasonic treatment for 60min;
[0088] S3. Centrifuge, wash, filter and vacuum dry the obtained product to constant weight to obtain organic zirconium phosphate.
[0089] (2) Preparation of polyurethane-zirconium phosphate composite modified asphalt
[0090] S1. Weigh the following components by weight: 100 parts of 70# matrix asphalt, 10 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 5 parts of organic zirconium phosphate prepared in step (1), 0.05 parts of catalyst (dibutyltin dilaurate) and 3 parts of solubilizer (dioctyl maleate, furfural extracted oil, epoxidized soybean oil and cashew nut shell oil);
[0091] S2. Add 70# base asphalt into a stirring tank, heat and maintain the temperature at 130°C, then add organic zirconium phosphate, solubilizer and catalyst into the stirring tank and stir for 30 minutes;
[0092] S3, preheating the isocyanate prepolymer to 90°C, adding it to the stirring tank in step S2, and continuing stirring for 60 minutes;
[0093] S4. After the stirring is completed, the mixture is placed in a temperature environment of 100° C. and allowed to stand for 6 hours to obtain an aging-resistant polyurethane-zirconium phosphate composite modified asphalt.
[0094] Comparative Example 1
[0095] The same as Example 1, except that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, the following components are weighed in parts by weight: 100 parts of 70# base asphalt, 2 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 5 parts of organic zirconium phosphate prepared in step (1), 0.001 parts of catalyst (dibutyltin dilaurate) and 3 parts of solubilizer (cashew nut shell oil).
[0096] The remaining steps are the same as in Example 1.
[0097] Comparative Example 2
[0098] The same as Example 1, except that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, the following components are weighed in parts by weight: 100 parts of 70# base asphalt, 18 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 5 parts of organic zirconium phosphate prepared in step (1), 0.001 parts of catalyst (dibutyltin dilaurate) and 3 parts of solubilizer (cashew nut shell oil).
[0099] The remaining steps are the same as in Example 1.
[0100] Comparative Example 3
[0101] The same as Example 1, except that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, the following components are weighed in parts by weight: 100 parts of 70# base asphalt, 10 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 0.5 parts of organic zirconium phosphate prepared in step (1), 0.001 parts of catalyst (dibutyltin dilaurate) and 3 parts of solubilizer (cashew nut shell oil).
[0102] The remaining steps are the same as in Example 1.
[0103] Comparative Example 4
[0104] The same as Example 1, except that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, the following components are weighed in parts by weight: 100 parts of 70# base asphalt, 10 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 10 parts of organic zirconium phosphate prepared in step (1), 0.001 parts of catalyst (dibutyltin dilaurate) and 3 parts of solubilizer (cashew nut shell oil).
[0105] The remaining steps are the same as in Example 1.
[0106] Comparative Example 5
[0107] The same as Example 1, except that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, the following components are weighed in parts by weight: 100 parts of 70# base asphalt, 10 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 5 parts of organic zirconium phosphate prepared in step (1) and 0.001 parts of catalyst (dibutyltin dilaurate).
[0108] The remaining steps are the same as in Example 1.
[0109] Comparative Example 6
[0110] The same as Example 1, except that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, the following components are weighed in parts by weight: 100 parts of 70# base asphalt, 10 parts of isocyanate prepolymer (polyether isocyanate prepolymer, molecular weight of 2000-4000, -NCO content of 9%), 5 parts of organic zirconium phosphate prepared in step (1), 0.001 parts of catalyst (dibutyltin dilaurate) and 7 parts of solubilizer (cashew nut shell oil).
[0111] The remaining steps are the same as in Example 1.
[0112] Comparative Example 7
[0113] The same as Example 1, the only difference is that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, S4 is: after the stirring is completed, the mixture is placed in a temperature environment of 100° C. and allowed to stand for 4 hours.
[0114] The remaining steps are the same as in Example 1.
[0115] Comparative Example 8
[0116] The same as Example 1, the only difference is that in the preparation process of the polyurethane-zirconium phosphate composite modified asphalt, S4 is: after the stirring is completed, the mixture is placed in a temperature environment of 100° C. and allowed to stand for 10 hours.
[0117] The remaining steps are the same as in Example 1.
[0118] Performance Testing
[0119] In order to verify the relevant performance of the aging-resistant polyurethane-zirconium phosphate composite modified asphalt, the softening point, penetration and ductility tests were performed on the above-mentioned base asphalt, the modified asphalt in the examples and the comparative examples to analyze the asphalt physical properties. In addition, the asphalt samples were subjected to UV aging tests (UV intensity 800W / m 2 , temperature is 60℃, aging time is 3 days), and a dynamic shear rheometer is used to perform temperature scanning experiments on the samples before and after aging, and the complex modulus aging index (CAI) and phase aging index (PAI) are calculated to evaluate the anti-aging ability of asphalt. The smaller the value of the complex modulus aging index and the larger the value of the phase aging index, the stronger the anti-aging ability of asphalt. The aging index calculation formula is as follows:
[0120]
[0121] Where: aging- represents the index after aging, and origin- represents the index before aging.
[0122] The performance test results are shown in Table 2.
[0123] Table 2 Asphalt physical properties and rheological aging index test results
[0124]
[0125]
[0126] Compare the performance of each asphalt sample in Table 2:
[0127] By comparing 70# base asphalt, Example 1, Comparative Example 1 and Comparative Example 2, it is shown that during the asphalt preparation process, the isocyanate prepolymer dosage is too low, and the physical properties have almost no modification effect compared to the base asphalt. If the isocyanate prepolymer dosage is too high, there is no further improvement in the overall asphalt compared to Example 1, so there is no need to increase the isocyanate prepolymer dosage.
[0128] By comparing Example 1, Comparative Example 3 and Comparative Example 4, it is shown that during the asphalt preparation process, the content of organic zirconium phosphate is too low, the formation of the cross-linking network in the modified asphalt is insufficient, and the physical properties of the asphalt are affected; although the content of organic zirconium phosphate is too high, it can further improve the anti-aging performance of asphalt, but it has a great negative impact on the low-temperature performance of asphalt.
[0129] By comparing Example 1, Comparative Example 5 and Comparative Example 6, it is shown that in the process of asphalt preparation, if the cashew nut shell oil content is too low, the asphalt will become hard and the anti-aging performance will be significantly reduced; if the cashew nut shell oil content is too high, the asphalt will be soft and the deformation resistance will be reduced.
[0130] By comparing Example 1, Comparative Example 7 and Comparative Example 8, it is shown that during the asphalt preparation process, the curing time is too short, the active group does not react fully with the isocyanate prepolymer, and the physical properties of the asphalt are affected; the curing time is too long, and there is almost no improvement on the overall performance of the asphalt, so there is no need to extend the curing time based on the recommended curing time.
[0131] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. An aging-resistant polyurethane-zirconium phosphate composite modified asphalt, characterized in that: The invention comprises the following components in parts by weight: 100 parts of base asphalt, 3 to 15 parts of isocyanate prepolymer, 1 to 8 parts of organic zirconium phosphate, 0.001 to 0.1 parts of catalyst and 2 to 5 parts of solubilizer; The organic zirconium phosphate is prepared by ultrasonically intercalating zirconium phosphate with organic molecules, wherein the organic molecules are polyamines, and the molar ratio of the organic molecules to the zirconium phosphate is (0.5-2):1; The isocyanate prepolymer includes a polyether isocyanate prepolymer and / or a polyester isocyanate prepolymer, wherein the isocyanate prepolymer is a polyether isocyanate prepolymer, has a molecular weight of 1000 to 5000, and a -NCO content of 3% to 18%; The method for preparing the aging-resistant polyurethane-zirconium phosphate composite modified asphalt comprises the following steps: Weigh each component by weight, heat and keep the base asphalt warm, then add the organic zirconium phosphate, solubilizer, and catalyst and stir, then add the heat-treated isocyanate prepolymer, continue stirring and let stand, to obtain the aging-resistant polyurethane-zirconium phosphate composite modified asphalt; The standing temperature is 80-120° C. and the standing time is 2-8 hours.
2. The aging-resistant polyurethane-zirconium phosphate composite modified asphalt according to claim 1, characterized in that: The base asphalt is road petroleum asphalt.
3. The aging-resistant polyurethane-zirconium phosphate composite modified asphalt according to claim 1, characterized in that: The solubilizing agent comprises one or more of dioctyl maleate, furfural extracted oil, epoxidized soybean oil and cashew nut shell oil.
4. The aging-resistant polyurethane-zirconium phosphate composite modified asphalt according to claim 1, characterized in that: The base asphalt is heated to 125-150° C., and the isocyanate prepolymer is preheated to 80-100° C. to obtain a heat-treated isocyanate prepolymer.
Citation Information
Patent Citations
Preparation method of polyurethane modified asphalt
CN102850506A
A method for preparing castor oil-based polyurethane modified bitumen and its mixture
CN106317371B
A petroleum road asphalt material and its preparation method
CN113861701B
Polyurethane modified asphalt and preparation method thereof
CN107177210A
Preparation method of polyurethane / organic montmorillonite composite modified asphalt
CN108485292A